Low Interest Rates and Banks' Interest Margins: Does Belonging to a Banking Group Matter? - Isabel Argimon; Jayson M. Danton; Jakob de Haan; Javier Rodriguez-Martin; Maria Rodriguez-Moreno (Center for Economic Studies and ifo Institute (CESifo), 2021)
Using data for a large sample of banks from 31 OECD countries over 1995–2018, we analyze the impact of belonging to a banking group on banks' net interest margins. Our results confirm a positive relationship between interest rates and interest margins, which is stronger in a low-interest rate environment. For banks belonging to an international banking group, we find that interest margins are less sensitive to the local interest rate. Our results show that banks belonging to an international group are sensitive to the interest rate prevailing in the group's headquarter, but only in a low interest rate environment.
Keywords: E43; E52; G21; 330; bank profitability; monetary policy transmission; net interest margin; low interest rates; banking groups